First human rabies case in French Guiana, 2008: epidemiological investigation and control. - Jean-Baptiste Meynard; Claude Flamand; Céline Dupuy; Aba Mahamat; Françoise Eltges; Frederic Queuche; Julien Renner; Jean-Michel Fontanella; Didier Hommel; Philippe Dussart; Claire Grangier; Félix Djossou; et al. (Public Library of Science (PLoS), 2012)
BACKGROUND: Until 2008, human rabies had never been reported in French Guiana. On 28 May 2008, the French National Reference Center for Rabies (Institut Pasteur, Paris) confirmed the rabies diagnosis, based on hemi-nested polymerase chain reaction on skin biopsy and saliva specimens from a Guianan, who had never travelled overseas and died in Cayenne after presenting clinically typical meningoencephalitis. METHODOLOGY/PRINCIPAL FINDINGS: Molecular typing of the virus identified a Lyssavirus (Rabies virus species), closely related to those circulating in hematophagous bats (mainly Desmodus rotundus) in Latin America. A multidisciplinary Crisis Unit was activated. Its objectives were to implement an epidemiological investigation and a veterinary survey, to provide control measures and establish a communications program. The origin of the contamination was not formally established, but was probably linked to a bat bite based on the virus type isolated. After confirming exposure of 90 persons, they were vaccinated against rabies: 42 from the case's entourage and 48 healthcare workers. To handle that emergence and the local population's increased demand to be vaccinated, a specific communications program was established using several media: television, newspaper, radio. CONCLUSION/SIGNIFICANCE: This episode, occurring in the context of a Department far from continental France, strongly affected the local population, healthcare workers and authorities, and the management team faced intense pressure. This observation confirms that the risk of contracting rabies in French Guiana is real, with consequences for population educational program, control measures, medical diagnosis and post-exposure prophylaxis.